An Integral Recognition and Signaling for Electrochemical Assay of Protein Kinase Activity and Inhibitor by Reduced Graphene Oxide-Polydopamine-Silver Nanoparticle-Ti4+ Nanocomposite - Wang, Jialong; Liu, Xueqian; Wang, Chao; Liu, Dengren; Li, Fang; Wang, Li; Liu, Shufeng (Frontiers in Bioengineering and Biotechnology, 2020)
A novel electrochemical biosensing method for protein kinase (PKA) activity was demonstrated by using a reduced graphene oxide-polydopamine-silver nanoparticles-Ti4+ (rGO-PDA-AgNPs-Ti4+) nanocomposite, which interestingly served as an integral phosphopeptide-recognizing and signal reporting platform. The polydopamine modified reduced graphene oxide (rGO-PDA) was first prepared by a self-polymerization method of dopamine. The silver ions were adsorbed onto polydopamine (PDA) layer and directly reduced into silver nanoparticles (AgNPs), which was used for electrochemical signal reporting. Then, the Ti4+ cations were attached onto the PDA layer for phosphopetide recognition according to the strong coordination ability of PDA with Ti4+ and phosphate group. The prepared rGO-PDA-AgNPs-Ti4+ nanocomposites were well-characterized by various techniques. With the full advantage of specific recognition of Ti4+ for the phosphate group, electrochemical response of AgNPs, and excellent conductivity of rGO, the rGO-PDA-AgNPs-Ti4+ nanocomposite endowed a label-free and one-step electrochemical analysis of kemptide phosphorylation catalyzed by PKA. The detection limit for PKA activity was experimentally achieved as 0.01 U/mL, which was evidently lower than most of the reported methods. The proposed sensing strategy could be also applied for an efficient inhibitor evaluation. Therefore, it offered an excellent pathway for a generic and sensitive electrochemical assay of PKA activity and inhibitor.